Pattern of Primary Vasculitis with Peripheral Ischemic Manifestations: Report of a Case Series and Role of Vascular Surgery - A. Gheita, Tamer; M. Abdel Samad, Hisham; A. Mahdy, Maher; B. Kamel, Alaa (Current Rheumatology Reviews, 2014)
Aim of the work: The aim of the present work was to study the role of vascular surgery in the management of primary vasculitis patients with peripheral ischemic manifestations. Patients and methods: Ten primary vasculitis patients with peripheral ischemic manifestations were studied and reviewed for the diagnosis, clinical manifestations, investigations, treatment options and role of vascular surgery. The Birmingham Vasculitis Activity Score (BVAS) was recorded. Results: Giant cell arteritis was present in one patient; granulomatosis with polyangiitis in 5, essential cryoglobulinemic vasculitis in 3 and 1 (child) had Henoch–Schönlein purpura. They showed the following peripheral vascular manifestations: intermittent claudications, Raynauds, deep venous thrombosis and thrombophelebitis in 10% each; digital ulceration and trophic changes in 20% while acrocyanosis and dry gangrene were present in 30%. Renal involvement was present in 60% of patients. The mean BVAS was 11.5±6.57 at initial presentation. The disease activity remarkably improved over the disease course in all patients to be at their last visit (2.6±2.22) (p=0.002). Regarding the vascular surgery role in their management, in addition to their medical treatment, 40% required an additional surgical intervention. Two had a minor amputation of the toes; one performed thoracoscopic cervical sympathectomy and another needed tibial angioplasty. Conclusion: Primary vasculitis patients presenting with peripheral ischemic manifestations require surgical attention. Their management is essentially medical and individualized to the diagnosis and presenting symptoms. Endovascular treatment may offer a safe and less invasive approach in high surgical risk patients. Sympathectomy is of high therapeutic potential in those with severe pain and trophic changes.
Keywords: vascular surgical procedures